A minimal model for household-based testing and tracing in epidemics. (19th May 2021) - Huber, Greg; Kamb, Mason; Kawagoe, Kyle; Li, Lucy M; McGeever, Aaron; Miller, Jonathan; Veytsman, Boris; Zigmond, Dan
Abstract: In a previous work (Huber et al. 2020 Phys. Biol. 17 065010), we discussed virus transmission dynamics modified by a uniform clustering of contacts in the population: close contacts within households and more distant contacts between households. In this paper, we discuss testing and tracing in such a stratified population. We propose a minimal tracing strategy consisting of random testing of the entire population plus full testing of the households of those persons found positive. We provide estimates of testing frequency for this strategy to work.